A Case Report Of Schatzker Type Vi Tibial Plateau Fracture Treated With Open Reduction And Internal Fixation Technique - Faldo Anshari Irza; Yoan Putrasos Arif (International Journal Labs, 2025)
Fractures of the tibial plateau are injuries that affect the upper part of the tibia. This fracture occurs in 1% of bone fracture cases. The bicondylar fractures of this structure are quite rare amongs the other type of tibial plateau fractures. Tibial Schatzker types VI have a high risk of complication such as delayed or nonunion and early post-traumatic osteoarthritis. Inadequate management of tibial plateau fractures can cause complication such as soft tissue healing problems, joint stiffness, arthritis, infection, malunion, and non-union. A Complex tibial plateau fractures require surgical intervention to give the best result. The most common surgical intervention for tibial plateau fractures is open reduction and internal fixation. Case Presentation: A previously healthy 16-year-old girl presented in a emergency room after being hit by a motorbike from the left side of the leg. Intervention : Open Reduction Internal and Fixation was done by this patient with plates and screw on both of lateral and medial side of the tibia. We got satisfactory result after performing this surgery. Outcome : The plateau tibia fracture were successfully reduced and got satisfactory result. Conclusion : The open reduction and internal fixation may have a satisfying result. The time between the injury occurs and the surgery treatment could make an important difference of the risk of complication.